The Oral Translator’s “Visibility”: The Chinese Translation of David Copperfield by Lin Shu and Wei Yi - Lung, Rachel (TTR)

(untitled) (Association canadienne de traductologie, 2004)
AbstractAn important feature in the translation history of China in the early 20th century was the collaboration between a Chinese monolingual and a Chinese bilingual in a large-scale translation of Western fiction. Such a collaboration pattern lasted for almost two decades before more Chinese bilinguals were trained in the 1920s. The partnership of Lin Shu (1852-1924) (a prominent written translator) and Wei Yi (1880-1933) (one of Lin Shu’s oral translators) lasted for 10 years, during which they translated over 40 English novels into Chinese. Through textual analyses of their co-translation of Charles Dickens’s David Copperfield in 1908, this article unravels the long-neglected contribution of Wei Yi in the work, and points to the importance of “orality” in their translation process in shaping Lin Shu’s translations. The article is structured into two parts: first, the background of Lin Shu and Wei Yi, and their collaboration; second, evidence of Wei Yi’s visibility in the translation in terms of textual changes from indirect speech to direct speech, the use of annotations, and the characteristics of the translation.